Methods for Incorporating Oxygen Generating Biomaterials into Cell Culture and Microcapsule Systems - McQuilling, John Patrick (Methods Mol Biol, 2017)
i. A major obstacle to long-term performance of tissue construct implants in regenerative medicine is the inherent hypoxia to which cells in the engineered construct are exposed prior to vascularization of the implant. Various approaches are currently being designed to address this problem. An emerging area of interest on this issue is the use of peroxide-based materials to generate oxygen during the critical period of extended hypoxia that occurs from the time cells are in culture waiting to be used in tissue engineering through the immediate post- implant period. In this chapter we provide protocols that we have developed for using these chemical oxygen generators in cell culture and tissue constructs as illustrated by pancreatic islet cell microencapsulation.